Histology an illustrated colour text - Mitchell, B.S (Illustrated colour text, 2009)
This volume in the Illustrated Colour Text series brings together high quality illustrations and a concise text focussed on essential features and is ideal for modern, medical undergraduate curricula where basic sciences emphasise the principle points of relevance to the students.